Nanofibrous PEDOT-Carbon Composite on Flexible Probes for Soft Neural Interfacing - Vajrala, Venkata Suresh; Saunier, Valentin; Nowak, Lionel G.; Flahaut, Emmanuel; Bergaud, Christian; Maziz, Ali (Frontiers in Bioengineering and Biotechnology, 2021)
In this study, we report a flexible implantable 4-channel microelectrode probe coated with highly porous and robust nanocomposite of poly(3,4-ethylenedioxythiophene) (PEDOT) and carbon nanofiber (CNF) as a solid doping template for high-performance in vivo neuronal recording and stimulation. A simple yet well-controlled deposition strategy was developed via in situ electrochemical polymerization technique to create a porous network of PEDOT and CNFs on a flexible 4-channel gold microelectrode probe. Different morphological and electrochemical characterizations showed that they exhibit remarkable and superior electrochemical properties, yielding microelectrodes combining high surface area, low impedance (16.8 ± 2 MΩ.µm2 at 1 kHz) and elevated charge injection capabilities (7.6 ± 1.3 mC/cm²) that exceed those of pure and composite PEDOT layers. In addition, the PEDOT-CNF composite electrode exhibited extended biphasic charge cycle endurance, resulting in a negligible physical delamination or degradation for long periods of electrical stimulation. In vitro testing on mouse brain slices showed that they can record spontaneous oscillatory field potentials as well as single-unit action potentials and allow to safely deliver electrical stimulation for evoking field potentials. The combined superior electrical properties, durability and 3D microstructure topology of the PEDOT-CNF composite electrodes demonstrate outstanding potential for developing future neural surface interfacing applications.